P139 Screening for child exploitation in online sexual health services: An exploratory study of expert views. (30th June 2016) - Spencer-Hughes, Victoria; Syred, Jonathan; Holdsworth, Gillian; Baraitser, Paula
Abstract : Background/introduction: Sexual health services routinely screen for child sexual exploitation. Although, sexual health services are increasingly provided online there has been no research on translation of the safeguarding function to online services. We studied expert views on safeguarding in this context. Aim(s)/objectives: To explore expert views on safeguarding within online sexual health services and their implications for service development. Methods: We conducted semi-structured interviews with local, regional and national experts purposively sampled to represent a wide range of organisations that have direct influence over CSE protocols, child protection policies and sexual health services. Interviews were analysed by three researchers using a matrix based analytic method. Results: Our respondents described two different approaches to safeguarding. The 'information providing' approach considers that young people, at risk of CSE, will ask for help, when they are ready from someone they trust. The primary function of the service is to provide information, generate trust and respond reliably to disclosure. The approach values online services as an anonymous space to test out disclosure without commitment. The 'information gathering' approach considers that young people may withhold information about exploitation. Services should therefore seek out information to assess risk and initiate disclosure. This approach values face-to-face opportunities for individualised questioning and immediate referral. Discussion/conclusion: The 'information providing' approach is associated with confidential telephone support lines and the 'information gathering' approach with clinical services. The approach adopted online will depend on ethos and the range of services provided. Effective transition from online to clinic services after disclosure is an essential element of this process and further research is needed to understand and support this transition.